(untitled) (Research, Society and Development, 2020)
Agricultural crops need protection from a variety of different insects popularly known as pests. Some of these pests are becoming increasingly resistant to conventional pesticides, so new control alternatives are needed. In this work, the effects of the essential oil of the plant Zanthoxylum caribaeum on the development of cotton stink bug Dysdercus peruvianus were analyzed. After analysis by chromatography and mass spectrometry, the essential oil of Z. caribaeum presented 54 substances, the main constituents being Sylvestrene, Muurola-4 (14), 5-trans-diene, Isodaucene and α-Pinene. These compounds significantly increased insect mortality and interrupted metamorphosis and molting, often in a dose-dependent manner. In addition, nymphs with deformed legs, wings and antennae were observed. According to the data, the components present in the essential oil of Z. caribeum appear to be promising candidates for the development of green insecticides for use in future integrated pest management (MIP) programs.